Financial Cost of Treating Polytrauma in a Public Tertiary Hospital in the South-Eastern Democratic Republic of Congo: A Case Series Study - Kabeya Diyoka C; Ngongo Mwanvua L; Shauri Kalemera M; Pambi Mukanga P; Koba Mjumbe C (ClinicoEconomics and Outcomes Research)
Chadrack Kabeya Diyoka,1 Laetitia Ngongo Mwanvua,1 Marcellin Shauri Kalemera,2 Pascal Pambi Mukanga,3 Criss Koba Mjumbe4 1School of Public Health, University of Lubumbashi, Lubumbashi, Democratic Republic of the Congo; 2Doctor of Medicine, University of Lubumbashi, Lubumbashi, Democratic Republic of the Congo; 3Department of Management of Health Policies and Service, School of Public Health, University of Kananga, Kananga, Democratic Republic of the Congo; 4Department of Public Health, Faculty of Medicine, University of Lubumbashi, Lubumbashi, Democratic Republic of the CongoCorrespondence: Criss Koba Mjumbe, Department of Public Health, Faculty of Medicine, University of Lubumbashi, Lubumbashi, Democratic Republic of the Congo, Email cryss_koba25@yahoo.frContext: Polytrauma constitutes a major public health issue that is steadily increasing. In developing countries, including the Democratic Republic of Congo, this phenomenon is exacerbated by a combination of factors, such as inadequate funding mechanisms, the high cost of healthcare services and the low socio-economic level of the populations at risk. This study aims to assess the financial cost of treating polytrauma in a tertiary hospital in the Democratic Republic of the Congo.Patients and Methods: A case series study was conducted at the Jason SENDWE provincial referral general hospital in Lubumbashi, with data collected from 1 January to 31 December 2023. The study was based on the operational definitions of Heinrich and the economic burden of care at the individual level was calculated by dividing the average direct costs by the GDP per capita, PPP of the country.Results: The present study comprised forty patients with polytrauma, with a mean age of 29.73 ± 9.9 years, ranging from 9 to 45 years.Approximately 65% of cases were attributed to road accidents, with a male predominance of 82.5%.The most frequently observed form of vital distress was neurological, accounting for 60% of cases, and le parage chirurgical comme acte chirurgical (28.11%). The overall survival rate was 7.50%, with a mean direct cost per patient of USD 608.77 ± 370.85 (range: USD 139.78 to USD 1826.34). This equates to a financial burden of 93.79 ± 57.13% of GDP per capita, ranging from 21.54 to 281.36% of GDP per capita.The proportion of out-of-pocket payments was 97.5%. The highest proportion of expenditure (42.2%) was attributed to medications, followed by the cost of surgical procedures (23.21%), and then imaging examinations (19.8%). Conversely, the lowest expenditure was observed to be related to resuscitation (1.21%) and laboratory tests (1.83%). It was observed that only polytrauma patients admitted to intensive care and hospitalised for 43 days or more exhibited a higher mean direct cost, with statistically significant differences (at a risk of 5%).Conclusion: Patients with polytrauma are at significant risk of incurring catastrophic health expenditures. The results provide insight into the financial implications of polytrauma, which may inform the organisation of trauma care.Keywords: polytrauma, cost-minimization analyses, management